Pre-Storage Leukoreduced Filtration (PLF) Decrease Soluble Human Leukocyte Antigen-I (sHLA-I) Level in Thrombocyte Concentrate Stored for Five Days - Herawati, S.; Sutirta-Yasa, I. W. P.; Suega, K.; Subawa, A. A. N. (BALI MEDICAL JOURNAL, 2016)
Background: Thrombocyte concentrate is one of the important blood component to improve patient's clinical condition. In order to provide thrombocyte, concentrate with good therapeutic effect, the preparation process and storage condition should be maintained properly. One attempt to maintain good quality of thrombocyte concentrates is by doing Pre-storage Leukoreduced Filtration (PLF) method during preparation of thrombocyte concentrates. The purpose of this study was to determine the effect of PLF on sHLA-I level in thrombocyte concentrates stored for 1, 3 and 5 days. Methods: This is an experimental study with posttest only Control Group design, enrolling 34 thrombocyte concentrates and randomly assigned into PLF Group and Control Group. Results: It was obtained that PLF Group has lower mean sHLA-I level than Control Group stored for 1, 3 and 5 days and statistically significant. Mean sHLA-I level in PLF Group at day 1 is 2,75±0,82 µg/ml and Control Group is 3,66±0,87 µg/ml, which is statistically significant (p < 0,05). Mean sHLA-I level in PLF Group at day 3 is 3,07±0,75 µg/ml and Control Group is 4,05±1,29 µg/ml, which is statistically significant (p < 0,05). Mean sHLA-I level in PLF Group at day 5 is 3,81±0,97 µg/ml and Control Group is 5,61±3,26 µg/ml, which is statistically significant (p < 0,05). Conclusions: It can be concluded that PLF decrease sHLA-I level in thrombocyte concentrates stored for five days compared with Control Groups.